Effects of Alcohol Cues on MRS Glutamate Levels in the Anterior Cingulate. (10th January 2018) - Cheng, Hu; Kellar, Derek; Lake, Allison; Finn, Peter; Rebec, George V; Dharmadhikari, Shalmali; Dydak, Ulrike; Newman, Sharlene
Abstract: Growing evidence suggests that glutamate neurotransmission plays a critical role in alcohol addiction. Cue-induced change of glutamate has been observed in animal studies but never been investigated in humans. This work investigates cue-induced change in forebrain glutamate in individuals with alcohol use disorder (AUD). A total of 35 subjects (17 individuals with AUD and 18 healthy controls) participated in this study. The glutamate concentration was measured with single-voxel 1 H-MR spectroscopy at the dorsal anterior cingulate. Two MRS sessions were performed in succession, the first to establish basal glutamate levels and the second to measure the change in response to alcohol cues. The changes in glutamate were quantified for both AUD subjects and controls. A mixed model ANOVA and t -tests were performed for statistical analysis. ANOVA revealed a main effect of cue-induced decrease of glutamate level in the anterior cingulate cortex (ACC). A significant interaction revealed that only AUD subjects showed significant decrease of glutamate in the ACC. There were no significant group differences in the level of basal glutamate. However, a negative correlation was found between the basal glutamate level and the number of drinking days in the past 2 weeks for the AUD subjects. Collectively, our results indicate that glutamate in key areas of the forebrain reward circuit is modulated by alcohol cues in early alcohol dependence.